M-stream deficits and reading-related visual processes in developmental dyslexia. [article]. - Boden, Catherine
Some visual processing deficits in developmental dyslexia have been attributed to abnormalities in the subcortical M stream and/or the cortical dorsal stream of the visual pathways. The nature of the relationship between these visual deficits and reading is unknown. The purpose of the present article was to characterize reading-related perceptual processes that may link the visual deficits to reading problems. We identified contrast sensitivity, position encoding, oculomotor control, visual attention, parafoveal/foveal interactions, and saccadic suppression as potential reading-related dorsal stream processes. We then evaluated the role of each process in reading and the status of each process in dyslexia. In theory, a number of dorsal stream processes (e.g., oculomotor control and visual attention) might contribute to reading problems in developmental dyslexia. More work is needed to demonstrate the connection empirically. -- (from the author)